Respuesta :

11x -7y= -14 (1)
x -2y= -4 (2)

Multiply (2) by 11, we have:
11x -22y= -44 (3)

Take (1)-(3), we have:
(11x-11x)+ (-7y-(-22y))= -14-(-44)
⇒ -7y+22y= -14+44
⇒ 15y= 30
⇒ y= 30/15
⇒ y= 2

x= -4+ 2y= -4+ 2*2= 0

The final answer is x=0, y=2~
The two given equations are
11x - 7y = - 14
x - 2y = -4
Now let us take the second equation for finding the value of x first
x - 2y = -4
x = 2y - 4
Now we have to put the value of x in the first equation
11x - 7y = - 14
11(2y - 4) - 7y = -14
22y - 44 - 7y = -14
15y = 44 - 14
15y = 30
y = 30/15
   = 2
Now let us put the value of y in the second equation
x - 2y = -4
x - 2(2) = -4
x - 4 = -4
x = -4 + 4
  = 0
So the value of x is 0 and the value of y is 2.